Mie Scattering by a Conducting Sphere Coated Uniaxial Single-Negative Medium - You-Lin Geng (International Journal of Antennas and Propagation)
We propose an accurate analytical method to compute the electromagnetic scattering from three-dimensional (3D) conducting sphere coated uniaxial anisotropic single-negative (SNG) medium. Based on the spherical vector wave functions (SVWFs) in uniaxial anisotropic medium, the electromagnetic field in homogeneous uniaxial SNG medium and free space can be expressed by the SVWFs in uniaxial SNG medium and free space. The continued boundary conditions of electromagnetic fields between the uniaxial SNG medium and free space are applied, and the tangential electrical field is vanished in the surface of conducting sphere, the coefficients of scattering fields in free space can be derived, and then the character of scattering of conducting sphere coated homogeneous uniaxial SNG medium can be obtained. Some numericals are given in the end.